Peran Salapan Cinyusu dalam Pelestarian Budaya Pangan Nabati Sunda dan Dampaknya terhadap Gastro-Tourism - Yumna Alifa; Affra Siti Nabilla; Wiwik Dwi Pratiwi (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
The Sundanese gastronomic tradition exhibits many cultural elements, including folklore, spiritual values, and mythology. It also encompasses a multitude of traditions, which collectively offer significant potential for further growth and development. One promising avenue for this growth is incorporating tourism approaches prioritising cultural resource conservation. Nevertheless, there currently needs to be more research investigating this potential, particularly concerning Sundanese plant-based gastronomy, which could be exploited as a distinctive feature of the city's tourism identity. This study examines the potential of gastronomy tourism as a strategy for preserving traditional Sundanese plant-based food and the role of Salapan Cinyusu in addressing related issues. This study uses a qualitative approach with descriptive analysis. The descriptive analysis technique was used to comprehensively explain, describe and evaluate the social and cultural facts found in the field. The findings indicated that there is still considerable scope for improvement in preserving and developing gastro-tourism in Bandung. Furthermore, there is a need for greater collaboration between the various elements of Salapan Cinyusu to realise Bandung's potential fully.